THE ROLE AND PLACE OF CIVIL SOCIETY INSTITUTIONS IN THE SPHERE OF ENSURING THE COUNTRY’S ENVIRONMENTAL SECURITY (Law and Safety, 2018)
It has been emphasized that the modern development of civil society and the activation of social movements in all spheres of public life require a rethinking of many forms and methods of participation of citizens in the management of public affairs. The scope of environmental safety and environmental protection is not an exception. It has been argued that citizens both individually and collectively, have the right to participate in the management of public affairs in the field of environmental safety, as well as to meet their own environmental needs and to protect environmental rights in any way not prohibited by law. It has been noted that the current legislation of Ukraine and international and legal acts consolidate the right of civil society institutions and individuals to participate in shaping state policy in the field of environmental safety and environmental protection as its necessary component.The normative and legal basis for the participation of civil society institutions in the field of environmental safety and environmental protection has been researched. The main types of such participation have been considered. Some directions of participation of citizens and their associations in the implementation of state policy in the field of environmental safety and environmental protection have been characterized. The main forms of participation of environmental NGOs and individual citizens in the implementation of state policy in the field of ensuring environmental safety of the state have been analyzed. The peculiarities of carrying out ecological examinations have been clarified.